Long Noncoding RNA and mRNA Expression Profiles in Rats with LPSinduced Myocardial Dysfunction - Han, Ye-Chen; Shen, Zhu-Jun; Xiang, Ruo-Lan; Lu, Bo; Qian, Hao; Li, Jing-Yi; Xie, Hong-Zhi (Current Genomics, 2022)
Background: Sepsis is an uncontrolled systemic inflammatory response. Long noncoding RNAs (lncRNAs) are involved in the pathogenesis of sepsis. However, little is known about the roles of lncRNAs in sepsis-induced myocardial dysfunction. Objective: We aimed to determine the regulatory mechanism of lncRNAs in sepsis-induced myocardial dysfunction. Methods: In this study, we analysed the lncRNA and mRNA expression profiles using microarray analysis. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, protein-protein interaction network, and gene set enrichment analysis were used to evaluate the data. We also constructed coding and noncoding coexpression and competing endogenous RNA networks to investigate the mechanisms. Results: In vivo lipopolysaccharide -induced sepsis rat model was established. A total of 387 lncRNAs and 1,952 mRNAs were identified as significantly changed in the left ventricle. Kyoto Encyclopedia of Genes and Genomes analysis of mRNAs showed that the upregulated genes were mainly enriched in the “complement and coagulation cascade pathway” and “immune-related biological processes” terms. Eight significantly changed lncRNAs detected by RT-qPCR may be responsible for these processes. A competing endogenous RNA network was generated, and the results indicated that eight lncRNAs were related to the “calcium ion binding” process. Conclusion: These results demonstrate that crosstalk between lncRNAs and mRNAs may play important roles in the development of sepsis-induced myocardial dysfunction.
Keywords: microarray